2004
DOI: 10.1592/phco.24.8.799.36062
|View full text |Cite
|
Sign up to set email alerts
|

Alendronate‐Induced Auditory Hallucinations and Visual Disturbances

Abstract: A 79-year-old Caucasian woman who had been taking alendronate 10 mg/day for over 2 years to prevent osteoporosis reported hearing "voices in her head" along with red-colored visual disturbances. These auditory hallucinations and visual disturbances began shortly after her regimen was changed from alendronate 10 mg/day to 70 mg once/week. Assessment of causality using the Naranjo and Jones algorithms revealed a "probable" and "highly probable" relationship, respectively, between this adverse drug event and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Bisphosphonates are currently the first-line therapeutic agents for treating postmenopausal women and men with osteoporosis, and patients with corticosteroid-induced osteoporosis [ 1 - 5 ]. While the vast majority of randomized controlled trial (RCTs) and observational studies demonstrated that bisphosphonates are both efficacious and promisingly safe in preserving bone density, preventing fragility fractures and reducing mortality [ 6 - 11 ], a few unexpected adverse effects, such as osteonecrosis of the jaw, hepatotoxity, auditory hallucination and visual disturbance have been increasingly described in the literature [ 12 - 15 ]. More recently, a RCT evaluating the efficacy and safety of zoledronic acid in postmenopausal women with osteoporosis demonstrated an unexpectedly higher risk of atrial fibrillation (AF) in patients who received the yearly intravenous zoledronate infusion compared to the control group [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bisphosphonates are currently the first-line therapeutic agents for treating postmenopausal women and men with osteoporosis, and patients with corticosteroid-induced osteoporosis [ 1 - 5 ]. While the vast majority of randomized controlled trial (RCTs) and observational studies demonstrated that bisphosphonates are both efficacious and promisingly safe in preserving bone density, preventing fragility fractures and reducing mortality [ 6 - 11 ], a few unexpected adverse effects, such as osteonecrosis of the jaw, hepatotoxity, auditory hallucination and visual disturbance have been increasingly described in the literature [ 12 - 15 ]. More recently, a RCT evaluating the efficacy and safety of zoledronic acid in postmenopausal women with osteoporosis demonstrated an unexpectedly higher risk of atrial fibrillation (AF) in patients who received the yearly intravenous zoledronate infusion compared to the control group [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alendronate (C 4 H 12 NO 7 P 2 Na·3H 2 O) is considered a first line option and normally taken orally when fasting, however it can be taken intravenously as well [15]. Some adverse effects include upper gastrointestinal intolerance [20] as well as auditory, visual, and olfactory hallucinations [21]. The chemical structure of Alendronate can be visualized in …”
Section: Bisphosphonatesmentioning
confidence: 99%